CRUISE TOURISM : PERSAINGAN IMAGE, VALUES DAN BRANDING DESTINASI WISATA - I Nyoman Sudiarta (Institut Pariwisata dan Bisnis Internasional, 2011)
Cruise tourism is a part of tourism industry, which kown as floating hotel or floating resort (Dowling (2006). It’s be a new industry in the world, that evidenytly the growth of cruises principal. Such as Holland American Line, Costa Cruise dan Carnival P&O Cruises, Silversea, Tui cruises, Star cruises. This opportunities supported The Growth of people travel used of cruise line average 4,5 % annual. Hence It’s will bring a tight competition especially in pricing play (Papatheodorou,2006). Bali as internation destination, owning opportunity as cruise tourist destination, with various weakness require or conducted research and correction of infrastructure and superstructure and also human resource that have ability in cruise tourism. Rivalry in the future between image and creating of value to the customer.